110k views
4 votes
Factor completely and then place the factors in the proper location on the grid. 20 y2 + 3 y - 2

User Saharsh
by
4.3k points

1 Answer

2 votes

Answer:

(4y - 1)(5y + 2)

Explanation:

Given

20y² + 3y - 2

Consider the product of the factors of the coefficient of the y² term and the constant term which sum to give the coefficient of the y- term.

product = 20 × - 2 = - 40 and sum = + 3

The factors are - 5 and + 8

Use these factors to split the y- term

20y² - 5y + 8y - 2 ( factor first/second and third/fourth terms )

= 5y(4y - 1) + 2(4y - 1) ← factor out (4y - 1) from each term

= (4y - 1)(5y + 2) ← in factored form

User Mayank Dudakiya
by
5.6k points